Pengaruh Naungan dan Dosis Fungi Mikoriza Arbuskular terhadap Pertumbuhan Kopi Arabika (Coffea arabica) Fase TBM - Yudithia Maxiselly; Ferrani Riefalina Nafy; Gina Savana Sarsan; Intan Ratna Dewi Anjarsari (Paspalum: Jurnal Ilmiah Pertanian, 2023)
The growth of Arabica coffee plants in the immature phase can be improved by shade application thus the plants absorb sunlight optimally and AMF to maintain soil fertility through the AMF association with the roots of the Arabica coffee plants. This research aims to determine the shading type and AMF dosage that increasing the growth of Arabica coffee plants (Coffea arabica) in the immature phase. This research was conducted at the Experimental Field of the Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang, West Java, with an altitude of Â±750 m above sea level from February 2023 to May 2023. The design used was a split plot design with three replications. The main plot was the type of shade which consisted of three levels, namely: 65% paranet shade, gamal shade trees with a ratio of gamal to coffee of 1:2, and shade trees of gamal with a ratio of gamal to coffee of 1:4. Subplots were AMF doses consisting of four levels: without AMF (control), AMF doses of 40g/plant, AMF doses of 50g/plant, AMF doses of 60g/plant. The results showed that there was an interaction effect between the shade of the gamal shade tree and the dose of AMF in the ratio of gamal to coffee 1:2 and the AMF dose of 40g/plant on the parameter of increase in stem diameter at 10-12 WAP. There is an independent effect of the type of shade of gamal shade trees with a ratio of gamal to coffee of 1:4 on the parameters of increase in leaf number 6-12 WAT, increase in branch length 2 WAT, increase in stem diameter 8-10 WAT, and chlorophyll index 2 WAT.